2016
DOI: 10.3138/cmlr.3605
|View full text |Cite
|
Sign up to set email alerts
|

Grammar Correction in the Writing Centre: Expectations and Experiences of Monolingual and Multilingual Writers

Abstract: Although most writing centres maintain policies against providing grammar correction during writing tutorials, it is undeniable that students expect some level of grammar intervention there. Just how much students expect and receive is a matter of speculation. This article examines the grammar-correction issue by reporting on a survey of L1, L2, and Generation 1.5 (Gen 1.5) writing-centre attendees. Results reveal that while all groups expected grammar help, L2 students expected the most. In addition, L1 and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The juxtaposed classroom and writing center data in this study reveal first-year multilingual writers who are interested in a variety of higher order and lower order concerns when they reflect on their own writing, providing further support for the conclusions of Eckstein (2016), Thonus (2014), . The division of addressing mostly "grammar" and "mistakes" at the writing center and addressing a combination of development and linguistic accuracy during self-reflections on writing and peer feedback may seem nothing less than natural for an L2 writing class.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The juxtaposed classroom and writing center data in this study reveal first-year multilingual writers who are interested in a variety of higher order and lower order concerns when they reflect on their own writing, providing further support for the conclusions of Eckstein (2016), Thonus (2014), . The division of addressing mostly "grammar" and "mistakes" at the writing center and addressing a combination of development and linguistic accuracy during self-reflections on writing and peer feedback may seem nothing less than natural for an L2 writing class.…”
Section: Discussionsupporting
confidence: 56%
“…As seen in these studies, whether tutors and writers believe that sentence-level feedback should be a significant part of writing center conversations, feedback on linguistic accuracy figures in many conversations about the writing center. Eckstein (2016) shows that international multilingual student writers may prefer that a writing center tutor "[p]oint out all of [their] grammar errors or edit [their] paper," and they agreed that grammar feedback was provided during their sessions (p. 368). Eckstein argues that "A stronger emphasis on grammar is due largely to pressure from university teachers who often recommend that L2 writers seek language help from tutors in the writing centre to correct their linguistic errors" (p. 362).…”
Section: Discussing "Grammar" With Multilingual Writers In the Writinmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, emphasis on student-centered instruction and the teacher's role as facilitator as explained by Lim & Griffith (2016) be considered in communicative language classroom. Specifically during the productive stages, the involvement of students in the writing process; prewriting, writing the drafts, and improving the drafts, is vital to the development of positive values towards the language learning and facilitate the learning strategies of the students (Eckstein, 2016). Hence, Chaudron (1998) emphasizes the exploration of peer correction or self-correction with teacher's guidance in empowering individual student's self-efficacy for he believes that in peer editing, students feel at ease when they interact with their peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the content of tutoring sessions, Eckstein (2016) discussed the intersection of writing tutor training, students' expectations, and what takes place during tutoring sessions. His study L1, Gen 1.5, and L2 users1 of the writing center found that students in each group expected some kind of grammar support in sessions.…”
Section: Addressing Content and Grammar Concernsmentioning
confidence: 99%